The proteasome regulates collagen-induced platelet aggregation via nuclear-factor-kappa-B (NFĸB) activation. Issue 148 (December 2016) - Grundler, Katharina; Rotter, Raffaela; Tilley, Sloane; Pircher, Joachim; Czermak, Thomas; Yakac, Mustaf; Gaitzsch, Erik; Massberg, Steffen; Krötz, Florian; Sohn, Hae-Young; Pohl, Ulrich; Mannell, Hanna; et al.
Abstract: Introduction: Platelets possess critical hemostatic functions in the system of thrombosis and hemostasis, which can be affected by a multitude of external factors. Previous research has shown that platelets have the capacity to synthesize proteins de novo and more recently a multicatalytic protein complex, the proteasome, has been discovered in platelets. Due to its vital function for cellular integrity, the proteasome has become a therapeutic target for anti -proliferative drug therapies in cancer. Clinically thrombocytopenia is a frequent side-effect, but the aggregatory function of platelets also appears to be affected. Little is known however about underlying regulatory mechanisms and functional aspects of proteasome inhibition on platelets. Our study aims to investigate the role of the proteasome in regulating collagen-induced platelet aggregation and its interaction with NFkB in this context. Material and methods: Using fluorescence activity assays, platelet aggregometry and immunoblotting, we investigate regulatory interactions of the proteasome and Nuclear-factor-kappa-B (NFkB) in collagen-induced platelet aggregation. Results: We show that collagen induces proteasome activation in platelets and collagen-induced platelet aggregation can be reduced with proteasome inhibition by the specific inhibitor epoxomicin. This effect does not depend on Rho-kinase/ROCK activation or thromboxane release, but rather depends on NFkB activation. Inhibition of the proteasome prevented cleavage of NFκB-inhibitor protein IκBα and decreased NFκB activity after collagen stimulation. Inhibition of the NFκB-pathway in return reduced collagen-induced platelet proteasome activity and cleavage of proteasome substrates. Conclusions: This work offers novel explanations how the proteasome influences collagen-dependent platelet aggregation by involving non-genomic functions of NFkB. Highlights: Platelet activation with collagen activates the proteasome and the NFkB pathway. Proteasome substrates IκBα and Filamin A are cleaved after collagen activation. Proteasome regulates platelet aggregation independent of thromboxane or Rho-Kinase. As a feedback mechanism NFkB affects platelet proteasome activity. The proteasome and NFkB appear mutually connected in collagen-induced aggregation.